Trí tưởng tượng của du khách trong đồng tạo sinh giá trị dịch vụ: Một nghiên cứu trong ngành du lịch - Nguyễn Thị Cẩm , Hiền; Bùi Huy Hải , Bích; Lê Nguyễn, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study explores the role of imagination, a personal capability of tourists, in their participation in the service value co-creation process. Using the data collected from 275 domestic tourists, Structural Equation Modeling (SEM) analysis results indicate the direct and indirect effects of imagination on the experience value through the mediation of three co-creation behaviors, including information sharing, responsible behavior, and personal interaction. Theoretical and managerial implications are then discussed accordingly.
Keywords: Customer imagination; Tourism service; Value co-creation; Experience value